Primary gastric adenosquamous carcinoma in an Indian male - Rinkesh Kumar Bansal; Praveen Sharma; Ramneet Kaur; Anil Arora (Wolters Kluwer Medknow Publications, 2013)
Adenosquamous carcinoma (ASC) of the stomach is a very rare tumor comprising less than 0.5% of all stomach malignancies. Here, we report a case of a 37-year-old male, who presented with upper gastrointestinal bleeding in the form of hematemesis and malena. A subtotal gastrectomy was done in view of massive uncontrolled bleed. Histology showed evidence of ASC of the body and antrum with metastasis to the liver, perigastric lymph nodes and peritoneal and pleural cavity.